The Influence of Attitudes and Risk Perceptions on Investment Decisions in Bank Syariah Indonesia (BSI) Shares - Yulia Cahya Ningrum; Fibrianis Puspita Anhar (Universitas Islam Negeri (UIN) Kiai Ageng Muhammad Besari Ponorogo, 2026)
Introduction: This article investigates the influence of attitudes and risk perceptions on investment decisions in shares of Bank Syariah Indonesia (BRIS). Research Methods: Employing a quantitative methodology, primary data were collected via a 1–4 Likert scale questionnaire. The research population consisted of 1,017 members of the “Syariah Saham” WhatsApp Group, from which a purposive sample of 91 respondents was drawn. Data analysis was conducted using multiple linear regression with SPSS 25. Results: The findings demonstrate that attitudes exert a positive and significant impact on investment decisions in BRIS shares. Similarly, risk perception is shown to have a positive and significant influence on investment decisions. Jointly, attitudes and risk perception significantly affect investment decision-making in BRIS shares. The coefficient of determination (R²) reveals that the model accounts for 64.9% of the variance in investment decisions. These results underscore the necessity of fostering positive attitudes and enhancing risk literacy to promote participation in sharia-compliant equity investments.